Middle‐Managerial Deviance as a Response to Structural Strain: Rescoping, Reconfiguring and Replacing Norms - Azambuja, Ricardo; Islam, Gazi (Journal of Management Studies, 2024)
AbstractThis paper examines how middle managers subvert organizational norms through diverse forms of deviance. Considering deviance not only in its negative sense, but including elements of adaptability and innovation, we draw on Mertonian theorizing around structural strains to explain deviance as resulting from mismatches between organizational norms and everyday work ‘on‐the‐ground’, with deviance practices feeding back iteratively into norm formation itself. Drawing upon observations, shadowing and interviews in a Brazilian accounting firm, we explore how deviance follows from incompatible pressures and norms across organizational levels and locations, and is realized in creative practical operationalizations of, and reaction to, conflicting norms. Through thick descriptions of three exemplary cases, we examine middle‐managerial deviance at varying level of detachment from, and dialogical relation to, norms. On this basis, we advance a multifaceted conceptualization of deviance – rescoping, reconfiguring and replacing norms – accounting for its conditions of emergence, diversity of mechanisms, and repercussions on middle managers' agency and organizational functioning and norms. Our findings demonstrate that deviance paves the way for new norm formation, reconciling contradictory constraints while consolidating middle managers' power over and beyond their official mandates.